Microwave pasteurisation for retention of bromelain and vitamin C in pineapple juice - Abd. Aziz, Nurul Azzah (2017)
The health benefits of bromelain and vitamin C attract a lot of interest from the consumers and food processing industries. Since it was known that conventional thermal treatment causes an adverse effect towards nutritional value in fruit juices, therefore a novel thermal processing such as microwave can become a potential alternative for juice pasteurisation. The main objective of this study is to evaluate the effect of microwave and conventional thermal pasteurisation on the quality of pineapple juice that includes bromelain proteolytic activity, vitamin C contents, microbial contents, colour and pH. The growth of microorganisms and changes in all parameters during storage period of 30 days were also studied. The pineapple juice sample was heated to 60°C on a hot plate with a stirrer and was held for 5 minutes in conventional thermal treatment. For microwave sample it was heated with an operating power of 900 W until the temperature reached 60°C and was held for 5 minutes. It was shown that microwaved samples had significantly (p<0.05) retained a higher amount of bromelain and vitamin C compared to conventional thermal treatment. The residual percentage of bromelain and vitamin C in microwaved juice were 87.36 ± 3.15% and 90.87 ± 1.13% whereas for conventional treated samples the values were reduced to 70.83 ± 7.01% and 74.72 ± 0.37%, respectively. At the end of the storage period, approximately 50% retention of bromelain and vitamin C were found in microwave treated juice. The degradation of these nutrients were rapid in conventional heated sample during storage. Both degradation of bromelain and vitamin C in microwaved and conventional pasteurised juices followed first order kinetic model. The k values of bromelain degradation were 0.0175 ± 0.0002 day-1 (microwave) and 0.0322 ± 0.0027 day-1 (conventional) while k values for vitamin C degradation were 0.0182 ± 0.001 day-1 (microwave) and 0.0257 ± 0.001 day-1. The shelf life of microwaved samples was 22 days compared to only 14 days for conventional pasteurised pineapple juice. No significant changes detected in pH values after treatment and storage, however, the differences in colour was well visible after 30 days in both pasteurised juices. Therefore, it can be concluded that microwave treatment is a potential alternative for fruit juice pasteurisation especially for small scale industrial application.